Physical separation of catalytic oxidation and reduction sites onto photocatalyst assisted by surface functional groups for enhanced hydrogen evolution. (15th November 2021) - Chen, Huajiao; Yu, Zebin; Jiang, Ronghua; Huang, Jun; Hou, Yanping; Chen, Jianhua; Zhang, Yongqing; Zhu, Hongxiang; Wang, Bing; Lian, Cuifang
Abstract: Physical separation of catalytic reduction and oxidation sites is a common approach in photocatalysis to optimize photogenerated charge separation and improve redox ability of catalysts. Herein, we report a novel site-directed photodeposition technology assisted by specific surface functional groups for the synthesis of Nix /NH2 –Cd0.5 Zn0.5 S–S 2- (Nix /N-CZS-S 2- ) catalyst. Two creative functions are exhibited. On the one hand, the surface functional groups –NH2 act as a bridge to anchor catalytic reduction center Ni, and this particular anchor form provides a new electron transfer channel for photocatalytic hydrogen evolution. On the other hand, the surface functional groups S 2− provides sites for holes that can be eliminated by the sacrificial agent. As a result, these two advantages guarantee the hydrogen evolution of the Ni2 /N-CZS-S 2- to reach 32, 025 μmol g −1 ·h −1 and the quantum yield to reach 25.68 % at 420 nm. This particular site-directed photodeposition technology can optimize charge transfer kinetics and improve redox reaction kinetics of catalyst. In addition, it can be extended to related systems as an effective strategy for enhanced photocatalysis performance.